2019
DOI: 10.18592/let.v9i2.3206
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Volition in Public Speaking Class Among the English Education Students in Sanata Dharma University

Abstract: Public speaking is frequently referred to as an anxiety-provoking activity. Volition is linked to individuals' willpower and persistence to face distraction in achieving particular goals. The aim of this study is exploring the volitional strategies used by English speaking class students and the factors that particularly influenced the students in dealing with the anxiety in public speaking. The participants are the 30 public speaking class students. This study used a questionnaire and interview as the instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(10 reference statements)
0
3
0
2
Order By: Relevance
“…Ultimately, (Suprapto, Chang, & Ku, 2017) and (Utami, 2017) conducted self-efficacy studies focusing on Physics learning processes and Entrepreneurial education. Furthermore, (Lomi & Mbato, 2019) mentioned that EFL learners urgently require continuous moral supports from their teachers to increase their volition and motivation in public speaking class. Mbato (2020) also reported that multiple learning strategies implemented in public speaking class do not only enable EFL learners to be proficient L2 speakers but also confident and qualified public speakers.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, (Suprapto, Chang, & Ku, 2017) and (Utami, 2017) conducted self-efficacy studies focusing on Physics learning processes and Entrepreneurial education. Furthermore, (Lomi & Mbato, 2019) mentioned that EFL learners urgently require continuous moral supports from their teachers to increase their volition and motivation in public speaking class. Mbato (2020) also reported that multiple learning strategies implemented in public speaking class do not only enable EFL learners to be proficient L2 speakers but also confident and qualified public speakers.…”
Section: Introductionmentioning
confidence: 99%
“…This research used a mixed-method design. Mixed method studies have been utilized by many Indonesian researchers, specifically in the field of education (Aini et al, 2020;Astriningsih & Mbato, 2019;Daud et al, 2019;Lomi & Mbato, 2019;Pardede, 2019). The aim of the combined methods was not to substitute quantitative or qualitative data but to combine both results by examining the findings of the entire study and drawing conclusions (Ivankova et al, 2006, p. 17).…”
Section: Methodsmentioning
confidence: 99%
“…En estos su aprendizaje se obstaculiza cuando están expuestos a explicaciones teóricas prolongadas, actividades repetidas, pasivas o detalladas o cuando trabajan de forma individual (Alonso et al, 1997). En caso de presentar dificultades en su proceso de aprendizaje, el uso de estrategias volitivas puede fortalecer su esfuerzo para mantenerse en el logro de sus metas académicas (Shih, 2019), en especial cuando hay distracciones como el aburrimiento, tedio o cansancio en las tareas académicas (Lomi & Mbato, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…En este sentido, un estudiante autorregulado es proactivo, autónomo y acepta la responsabilidad en sus tareas académicas. Dentro de los procesos autorregulatorios se encuentran los volitivos, que permiten cumplir y proteger las metas académicas de distracciones y dificultades, y son necesarios para mantener el deseo por el aprendizaje hasta el logro de la meta propuesta, en especial ante el aburrimiento, el tedio, el cansancio o el estrés por las tareas académicas (Lomi & Mbato, 2019).…”
Section: Introductionunclassified